Deep Ion Torrent sequencing identifies soil fungal community shifts after frequent prescribed fires in a southeastern US forest ecosystem - Brown, Shawn Paul; Callaham, Mac A., Jr; Oliver, Alena K.; Jumpponen, Ari M. (My University, 2014)
Prescribed burning is a common management tool to control fuel loads, ground vegetation, and facilitate desirable game species. We evaluated soil fungal community responses to long-term prescribed fire treatments in a loblolly pine forest on the Piedmont of Georgia and utilized deep Internal Transcribed Spacer Region 1 (ITS1) amplicon sequencing afforded by the recent Ion Torrent Personal Genome Machine (PGM). These deep sequence data (19,000+ reads per sample after subsampling) indicate that frequent fires (3 year fire interval) shift soil fungus communities whereas infrequent fires (6 year fire interval) permit system resetting to a state similar to that without prescribed fire. Furthermore, in nonmetric multidimensional scaling analyses, primarily ectomycorrhizal taxa were correlated with axes associated with long fire intervals whereas soil saprobes tended to be correlated with the frequent fire recurrence. We conclude that 1) multiplexed Ion Torrent PGM analyses allow deep cost effective sequencing of fungal communities, but may suffer from short read lengths and inconsistent sequence quality adjacent to the sequencing adaptor; 2) frequent prescribed fires elicit a shift in soil fungal communities; and, 3) such shifts do not occur when fire intervals are longer. Our results emphasize the general responsiveness of these forests to management, and the importance of fire return intervals in meeting management objectives.
Keywords: Fungi; Ion Torrent PGM; Lightless sequencing; Prescribed fire; Soil